Success Factors of JIT Integration with IBS Construction Projects– A Literature Review - Mohammad Azwanie Naim Mohammad Asri; Mohd Nasrun Mohd Nawi; Santhirasegaran Nadarajan; Wan Nadzri Osman; Aizul Nahar Harun (International Journal of Supply Chain Management, 2016)
The Just-In-Time (JIT) philosophy has been used for many decades to increase productivity through waste elimination process. The purpose of this paper is to contribute to the body of knowledge by addressing the issue of transportation, logistic and material delivery in Industrialized Building System (IBS) construction projects. This paper through literature review aims to highlight this issue by investigate the key success factors for integrating JIT and IBS in the Malaysian construction industry. Suggestion on how the concept of JIT can contribute for improving the performance of transportation and material delivery activities in IBS projects will be concluded.